1948
DOI: 10.1172/jci101948
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Chemotherapy of the Human Malarias. Viii. The Physiological Disposition of Pamaquine 123

Abstract: The recent appreciation (1, 2) of the earlier studies on the curative activity of pamaquine in mosquito-transmitted vivax malaria (3) has promoted renewed interest in the chemotherapeutic potentialities of this compound and of several related derivatives of 8-aminoquinoline. Consequently, a report on the physiological disposition of pamaquine seemed desirable. METHODS AND MATERIALThe individuals used in these studies were, for the most part, patients with central nervous system syphilis. Certain of the pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1948
1948
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Workers in the late 1940s and 1950s showed that pamaquine (Zubrod, Kennedy & Shannon, 1949) and pentaquine (Elderfield & Smith, 1953) were rapidly removed from the body and almost entirely metabolized. These studies, however, suffered from a lack of specific and sensitive techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Workers in the late 1940s and 1950s showed that pamaquine (Zubrod, Kennedy & Shannon, 1949) and pentaquine (Elderfield & Smith, 1953) were rapidly removed from the body and almost entirely metabolized. These studies, however, suffered from a lack of specific and sensitive techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism responsible for this effect is unknown. It is of interest to note that quinacrine has a similar effect on the concentration of pamaquin in plasma (17).…”
Section: Effectiveness Of Palidrine In Vivax Malariamentioning
confidence: 99%
“…Pamaquine exposure seems to be increased by the coadministration of quinacrine. 18 In four patients, pamaquine concentrations after coadministered drug were at least six times the level before quinacrine was administered, and the half-lives approximately quadrupled. Clayman and others 16 found a dose-related decrease in primaquine concentrations with coadministration with quinine from no apparent effect at 22.5 mg to a 50% reduction at 120 mg primaquine.…”
mentioning
confidence: 93%
“…After oral dosing of pamaquine in humans, peak serum levels are achieved at approximately 3 hours, and then, they decline with a half-life of approximately 2 hours. 18 Zubrod and others 18 also commented that the "pathway of metabolism of the drug is not known. [There is e]vidence for the presence of two metabolic intermediates."…”
mentioning
confidence: 99%
See 1 more Smart Citation